Cancer Immunoimaging with Smart Nanoparticles. Issue 4 (April 2020) - Ou, Yu-Chuan; Wen, Xiaona; Bardhan, Rizia
Abstract : Dynamic immunoimaging in vivo is crucial in patient-tailored immunotherapies to identify patients who will benefit from immunotherapies, monitor therapeutic efficacy post treatment, and determine alternative strategies for nonresponders. Nanoparticles have played a major role in the immunotherapy landscape. In this review, we summarize recent findings in immunoimaging where smart nanoparticles target, detect, stimulate, and deliver therapeutic dose in vivo . Nanoparticles interfaced with an immunoimaging toolbox enable the use of multiple modalities and achieve depth-resolved whole-body tracking of immunomarkers with high accuracy both before and after treatment. We highlight how functional nanoparticles track T cells, dendritic cells (DCs), tumor-associated macrophages (TAMs), and immune checkpoint receptors (ICRs), and facilitate image-guided interventions. Highlights: Dynamic imaging of immune cells that have a crucial role in the progression or suppression of tumors has transformed the landscape of cancer immunotherapies, allowing clinicians to predict the best treatment strategies and monitor treatment response. Tracking immune cells in vivo with smart nanoparticles is beneficial because multiple imaging modalities have been successfully integrated on a single nanoscale platform, enabling depth-resolved whole-body detection with high sensitivity and specificity of tumors that overexpress immunomarkers. Smart nanoparticles have also enabled image-guided interventions, where nanoparticles with both diagnostic and therapeutic ability were labeled to immune cells and tracked in vivo, followed by antigen delivery. Such theranostic nanovaccines elicit robust and persistent antigen-specific immune responses with dynamic visualization of therapeutic efficacy.